Echocardiography in the Assessment of Left Atrial Pressure After Pediatric Heart Surgery: A Comparison Study With Measurements Obtained From Left Atrial Catheter. (July 2015) - Figueras-Coll, Marc; Sanchez-de-Toledo, Joan; Gran, Ferran; Abella, Raul; Perez-Hoyos, Santiago; Rosés, Ferran
Background: Correlation between ventricular end-diastolic pressure and pulsed Doppler and tissue Doppler–derived E/e' ratio has been widely reported in adults but scarcely studied in children with congenital heart diseases. This ratio is defined as the relationship between diastolic transmitral flow velocity (cm/s; E) and myocardial diastolic relaxation velocity (cm/s; e') in the lateral aspect of the mitral annulus. Our main objective was to ascertain whether a correlation existed between direct measurement of left atrial pressure and echocardiographic E/e' ratio in children after heart surgery. Methods: Prospective study including 27 consecutive children after pediatric heart surgery. Data were analyzed according to whether they were obtained within the first 72 hours following surgery or later on. Sensitivity, specificity, positive and negative predictive values, and areas under the receiver–operating characteristics curve of E/e' ratio in detection of left atrial pressure values ≥13 mm Hg were evaluated. Results: Forty-eight studies were conducted in 27 patients. Thirty-two studies were performed during the first 72 hours after heart surgery and 16 beyond the third day. Median patient age was 0.82 years (5 days-16 years). Median left atrial pressure values and E/e' measurements of the whole cohort (N = 48) were 12.0 and 10.2, respectively. Intraclass correlation index between left atrial pressure values and echocardiographic E/e' ratio was 0.35, 0.25 for studies performed within 72 hours, but 0.78 ( P < .01) for those performed later. There was also a high positive predictive value, since in 13 (87%) of 15 studies with an E/e' ratio ≥13, the left atrial pressure was ≥13 mm Hg. Conclusion: While echocardiographic E/e' ratio did not show a good correlation with left atrial pressure in the immediate postoperative period, the positive predictive value may suffice to aid clinicians in predicting elevated pressures.